Gobernanza universitaria en tiempos de crisis sociosanitaria: experiencias de directivos chilenos (2020)
This article corresponds to a qualitative study that, through grounded theory, sought to understand the challenges that management teams must face in the context of university governance in times of social and sanitary crisis. To do so, focused interviews were conducted with 12 top-level managers who were working in various regional Chilean universities at the time of the crisis caused by the COVID-19, and who had to modify their face-to-face administrative and academic work to teleworking/online form. Thus, five major categories of analysis were identified: preparation for the crisis, strengths, difficulties, challenges and lessons learned resulting from management in times of pandemic. On the other hand, the challenges in the area of relational competencies that favor leadership and management are observed.